Cryo-EM structure of ABCG5/G8 in complex with modulating antibodies - Zhang, Hanzhi (Commun Biol, 2021)
The heterodimer of ATP-binding cassette transporter ABCG5 and ABCG8 mediates the excretion of sterols from liver and intestine, playing a critical role in cholesterol homeostasis. Here, we present the cryo-EM structure of ABCG5/G8 in complex with the Fab fragments from two monoclonal antibodies at 3.3Å resolution. The high-resolution structure reveals a unique dimer interface between the nucleotide-binding domains (NBD) of opposing transporters, consisting of an ordered network of salt bridges between the conserved NPXDFXXD motif and serving as a pivot point that may be important for the transport cycle. While mAb 11F4 increases the ATPase activity potentially by stabilization of the NBD dimer formation, mAb 2E10 inhibits ATP hydrolysis, likely by restricting the relative movement between the RecA and helical domain of ABCG8 NBD. Our study not only provides insights into the structural elements important for the transport cycle but also reveals novel epitopes for potential therapeutic interventions.